Occupational stress profiles of prehospital and clinical staff in emergency medicine—a cross-sectional baseline study - Meyer, Christine; Chiapponi, Costanza; von Kaufmann, Florentin; Kanz, Karl-Georg; Hinzmann, Dominik (Frontiers in Public Health, 2024)
Background Occupational stress among emergency medical staff remains a central problem. Prior to the COVID-19 pandemic, many studies were focused on the working conditions of clinical emergency staff, but few examined the occupational stress profiles of prehospital emergency dispatchers (ED). The aim of this study is therefore to provide baseline data on the differences in occupational stress profiles between prehospital and clinical emergency medical staff. Methods ED, emergency nurses (EN), and trauma surgeons on duty (TS) were questioned using the established and validated standardized short version of the instrument for stress-related job analysis for hospital physicians (ISAK-K). Differences between occupational groups were compared using the Mann–Whitney U test. Results Our data indicate significant differences in perception of stressors between professional groups (p < 0.05), with ED showing the highest psychological stress, followed by EN. Social stressors and emotional dissonance were significantly higher in ED and EN compared to TS (p < 0.05). Time pressure was identified as major stressor for ED and TS, but not for EN (p < 0.01). All professions showed moderate high levels of uncertainty and frustration (p = n.s.). Support from colleagues and supervisors was the greatest positive resource for all professional groups (p = n.s.). Conclusion In accordance with current literature, our results advocate for a re-evaluation of the identified stressors, as ED, EN, and TS continue to show high levels of occupational stress. Training programs for coping with emotional dissonance and social stressors are likely to be crucial for reducing job stress among ED and EN.